2004
DOI: 10.1002/cncr.20212
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy is not accurate in predicting lymph node status for patients with cervical carcinoma

Abstract: BACKGROUNDThe authors evaluated the accuracy of sentinel lymph node biopsy in predicting lymph node status for patients with early cervical carcinoma. In particular, the authors set out to determine the false‐negative rate associated with sentinel lymph node biopsy in this setting.METHODSTwenty‐nine consecutive patients with early cervical carcinoma who were treated with pelvic laparoscopic lymphadenectomy and radical surgery underwent sentinel lymph node biopsy following lymphatic mapping with patent blue dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
9

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 33 publications
0
36
0
9
Order By: Relevance
“…Immunohistochemical staining for tumor markers improves the sensitivity of micrometastasis detection and, when combined with serial sectioning to reduce the sampling error, results in upstaging of a significant number of patients. Some studies (7,8) have shown that doing additional tissue sections and/or immunohistochemistry of lymph node increases metastases detection, whereas other studies (9 -11), including our previous study (12), found that immunohistochemistry could not increase the detection rate of lymph node metastases in cervical cancer.…”
mentioning
confidence: 71%
“…Immunohistochemical staining for tumor markers improves the sensitivity of micrometastasis detection and, when combined with serial sectioning to reduce the sampling error, results in upstaging of a significant number of patients. Some studies (7,8) have shown that doing additional tissue sections and/or immunohistochemistry of lymph node increases metastases detection, whereas other studies (9 -11), including our previous study (12), found that immunohistochemistry could not increase the detection rate of lymph node metastases in cervical cancer.…”
mentioning
confidence: 71%
“…There has been a case reported of recurrence after Time ( sentinel node dissection where subsequent analysis confirmed that the negative sentinel node did contain micrometastases (Tamussino et al, 2002). Marchiole et al (2004) found that three out of five patients with nodal micrometastases in cervical cancer had tumour cells in nonsentinel nodes despite having negative findings. The high false negative rate with sentinel node biopsy in cervical cancer raises concerns about the accurate identification of sentinel nodes in this condition, which is in stark contrast to vulval cancer where the identification of sentinel nodes has been extensively studied with a higher predictive value.…”
Section: Discussionmentioning
confidence: 96%
“…The prediction of lymph node positivity will assist in developing adequate treatment options for patients since histologically undetectable micrometastases in the lymphatic system may account for cervical cancer recurrence. [27][28][29] Histological examinations are not infallible since examinations only comprise a small portion of lymph nodes, and estimates indicate that a pathologist has a 1% chance of detecting a micrometastatic focus within a three-tumor-cell diameter. 28,30 Gene amplification is a common mechanism for oncogene activation in tumorigenesis and gains on chromosomes 1q, 3q, and 5p are frequently observed in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%